IDENTIFIKASI NASIONALISME PADA KARYA KOIL DAN PAS BAND MELALUI PENDEKATAN DIALEKTIKA PEMAHAMAN DAN PENJELASAN MENURUT PAUL RICOEUR - Ajie, Sophan; Sihombing, Edy Syahputra; Kurniasih, Kurniasih (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This research aims to identify the interpretation of nationalism from the songs "Reality in the World Fantasy" by the music group Koil and Impresi by the "Pas Band" through the dialectic of interpreting displayed in the songs of the two bands. In addition, this study seeks to find the correlation of Pas Band and Koil's works with social reality to find out the philosophical impact obtained from the listeners, so that through them they can observe the understanding of the musical appreciator nationalism of the two bands who are also Indonesian citizens. The study uses Paul Ricoeur's hermeneutic theory in interpreting text (lyrics) and constructed aesthetic attributes such as screaming, video clips, relevant art work, and reactions of appreciators who listen to songs from Koil and Pas Band musical works. The research method is a qualitative description that takes an inventory of the works of the two bands and Paul Riseour's hermeneutic literature as secondary data. The results of this study are expected to find the meaning of nationalism that is stored in the works of Koil and Pas Band, as well as identify the nationalism of the music appreciators, the majority of whom are the younger generation as agents of the future and are responsible for the relay of the process of developing a nationalist mentality in order to maintain the unity of Indonesia.